THE INFLUENCE OF MORPHOLOGICAL AWARENESS TO COLLEGE STUDENTS’ VOCABULARY MASTERY - Sri Devi Apriyani; Ridha Ilma (Universitas Tridinanti Palembang, 2020)
Vocabulary is an element of language that has function to support the use of other elements of language (grammar, pronunciation, and spelling) and also to facilitate the use of four language skills. Morphological awareness is system that expected can help students to improve their vocabulary mastery. Objective of this study was to find out whether or not there was a significant correlation between morphological awareness and vocabulary mastery. Correlation study was used as research design. Sample of this study was fifty-six of 4th, 6th, 8th, and 10th semester undergraduate EFL students of Tridinanti University Palembang. Morphological awareness and vocabulary test were used as instruments. Morphological awareness test had 3 parts consisting of 45 items. Correlation analysis was used to examine correlation between morphological awareness and vocabulary mastery. Regression analysis was used to find out whether or not morphological awareness gave contribution to students’ vocabulary mastery. Then, vocabulary test consisted of 50 items. The result showed that there was a significant correlation between students’ morphological awareness and their vocabulary mastery but it was fair correlation. Moreover, morphological awareness contributed as much 21.9% toward students’ vocabulary mastery. Therefore, cultivating morphological awareness could be applied as a right strategy to improve students’ vocabulary mastery.Keywords: morphological awareness, vocabulary mastery.